Minimum delay algorithm based on time aggregated graph in DTN network - Peng WANG; Hong-yan LI; Tao ZHANG; Peng-yun LI (Tongxin xuebao)
The DTN network has the characteristics of dynamic topology change,thus the routing algorithm of static network can not solve the routing problem of time-varying network,and can not support fast transmission of given tasks.The existing time-variant routing algorithm CGR (contact graph routing) uses the earliest contact to obtain the shortest path,but because of the influence of the order of the connectivity period,the CGR algorithm has low link utilization.To solve this problem,the method of finding the shortest path was proposed.Besides,in order to characterize the relation between the different connect periods of the same link,the time series of node cache was added to the time aggregated graph.Based on this,the end-to-end multi-path shortest delay routing algorithm for the known task requirements was proposed.Finally,the feasibility of the algorithm was proved by an example.